A meta-analysis of clinical effects of microscopic unilateral laminectomy bilateral decompression (ULBD) versus biportal endoscopic ULBD for lumbar canal stenosis - Lin, Guang-Xun; Yao, Zhi-Kang; Xin, Chen; Kim, Jin-Sung; Chen, Chien-Min; Hu, Bao-Shan (Frontiers in Surgery, 2022)
Objective: Several studies have shown that both microscopic unilateral laminotomy bilateral decompression (ULBD) and unilateral biportal endoscopic (UBE) ULBD are effective for treating lumbar canal stenosis (LCS). However, there are different viewpoints as to which surgical technique is superior. Therefore, this meta-analysis investigated the clinical efficacy and side effects of microscopic ULBD and UBE ULBD for treating LCS. Methods: To identify relevant studies describing the clinical outcomes and complication rates of microscopic ULBD and UBE ULBD for LCS, several databases were systematically searched in the Internet. The visual analog scale score for back and leg pain and the Oswestry Disability Index were used to assess clinical outcomes. Furthermore, data about perioperative outcomes and complications were documented. Results: In total, six studies with 450 participants were included in this meta-analysis. The UBE ULBD was found to be superior to microscopic ULBD in terms of efficacy against early postoperative back and leg pain. However, there was no significant difference between the two procedures in terms of final clinical outcomes and complications. In addition, compared with microscopic ULBD, UBE ULBD was associated with a significant reduction in the length of hospital stay and C-reactive protein levels 2 days after surgery. Conclusion: UBE ULBD and microscopic ULBD for the treatment of LCS were similar in terms of final clinical outcomes and complications. However, UBE ULBD has several advantages over microscopic ULBE, including a shorter hospital stay and faster alleviation of postoperative back and leg pain.